Grusonia pulvinata, a new sibling species within G. vilis s.l. (Opuntioideae: Cactaceae) - Donati, Davide (Phytotaxa, 2025)
Grusonia pulvinata, a sibling new species endemic to alluvial plains of northern San Luis Potosì and adjacent area of Zacatecas (Mexico), is hereby described. The new species is morphologically very similar to G. vilis, from which differs by its strong joint junctions, high propensity to sexual reproduction, ecology, kariology and other minor traits with some affinities with Grusonia aggeria. A new combination is also proposed here: Grusonia grahamii subsp. vilis comb. et stat. nov.